건축물 유형별 침수취약곡선 기반의 도시지역 침수피해액 산정기법 개발 - 장동민; 박성원; Jang, Dongmin; Park, Sung Won (KSCE Journal of Civil and Environmental Engineering Research, 2024)
Severe casualties and property damage are occurring due to urban floods caused by extreme rainfall. However, there is a lack of research on preparedness, appropriate estimation of flood damages, assessment of losses, and compensation. Particularly, the flood damage estimation methods used in the USA and Japan show significant differences from the domestic situation, highlighting the need for methods tailored to the Korean context. This study addresses these issues by developing an optimized flood damage estimation technique based on the building characteristics. Utilizing the flood prediction solution developed by the Korea Institute of Science and Technology Information (KISTI), we have established an optimal flood damage estimation technology. We introduced a methodology for flood damage estimation by incorporating vulnerability curves based on the inventory of structures and apply this technique to real-life cases. The results show that our approach yields more realistic outcomes compared to the flood damage estimation methods employed in the USA and Japan. This research can be practically applied to procedures for flood damage in urban basement residences, and it is expected to contribute to establishing appropriate response procedures in cases of public grievances. 극한강우로 인한 도심지 침수피해는 극심한 인명 및 재산피해를 유발해왔으나 이를 대비하는 연구와 적절한 침수 피해 추정과 피해액의 산정 및 보상에 관한 연구가 미흡한 실정이다. 특히 미국이나 일본에서 적용되는 피해액 산정기법의 경우 재난 피해발생 양상이 국내와 큰 차이를 나타내기 때문에 국내 실정에 적합한 피해액 산정기법이 필요하다. 본 연구에서는 위와 같은 문제점에 착안하여 건물 특성별 최적화된 침수피해 추정기술 도출 방안을 마련하고 한국과학기술정보연구원(Korea Institute of Science and Technology Information, KISTI)에서 개발한 침수 예측 솔루션을 연계한 최적화된 침수피해액 추정기술 도출 방안을 마련하였다. 구조물 인벤토리별 침수취약곡선 추정방안을 적용하여 침수피해액을 산정하는 기법을 개발하고 실제 피해사례에 적용하였다. 그 결과, 미국 및 일본에 사용되고 있는 피해액 산정기법의 일괄적인 결과에 비해 현실적인 결과를 도출하여 비교하였으며 이를 통해 본 연구에서 개발 및 적용한 기술은 우리나라의 수도권 지역에 주로 분포하고 있는 도심지 반지하 주거형태의 실질적인 피해보상절차에 활용될 수 있고 민원 발생에 따른 적절한 대응 절차 마련 및 개선에 활용될 것으로 기대한다.